IMPLEMENTATION OF CONTEXTUAL APPROACH IN INDONESIAN LANGUAGE LEARNING IN STUDENTS' CREATIVE WRITING MATERIALS AT MI AL-KHAIRAAT PAKULI - Inna Ahyatun; Rusdin Rusdin; Rustam Rustam (IBTIDAI'Y DATOKARAMA: JURNAL PENDIDIKAN DASAR, 2025)
The purpose of this study is to determine how the application of the contextual approach in learning Indonesian language on creative writing material for students at MI Al- Khairaat Pakuli and to determine the results of its application. This study uses a qualitative method with a descriptive approach and a case study research design. The subjects of this study were students of class V MI Al-Khairaat and homeroom teachers. The data collection methods used were observation, interviews and documentation. Data obtained through the three methods were analyzed using qualitative descriptive. The results of this study indicate that (1) teachers in implementing or applying the contextual approach to learning Indonesian have been carried out well because teachers have understood the steps in implementing the contextual approach so that they are in accordance with the concepts and strategies. This can be seen from the average student who has achieved the KKM determined by the teacher. (2) factors that influence the success of teachers in implementing the contextual approach to learning Indonesian are teacher factors, student factors, facilities and infrastructure and environmental factors. Implications of the research Students are expected to be more active in participating in the learning process and students must be more focused on the learning process in class, especially when the teacher is explaining the material so that students can more easily absorb the knowledge that has been conveyed by the teacher.